A stochastic techno‐economic analysis of the catalytic hydrothermolysis aviation biofuel technology. (22nd February 2018) - McGarvey, Elspeth; Tyner, Wallace E.
Abstract: This study analyzed the financial feasibility of catalytic hydrothermolysis (CH) aviation biofuel technology. Three feedstocks were assessed: brown grease (rendered from grease trap waste), yellow grease (rendered from used cooking oil), and carinata oil. Since the technology carries risk, a stochastic analysis was conducted, which resulted in a distribution of net present values (NPVs) and breakeven prices. The breakeven price was the price of jet fuel per gallon that made the NPV equal to zero. A scenario where fuel price grew over time and a scenario where fuel price did not grow were both analyzed. Four plant scenarios were analyzed: 1. pioneer brownfield, 2. N th brownfield, 3. pioneer greenfield, 4. Nth greenfield. Brown grease was the most promising feedstock scenario, in terms of financial feasibility. Breakeven prices in each feedstock scenario were lowest in the brownfield n th plant scenario, and highest in the greenfield pioneer plant scenario. Across the four plant scenarios and two fuel price growth scenarios, mean breakeven prices ranged from 2.02 to 2.83/gal in the brown grease scenario, 2.82 to 3.81/gal in the yellow grease scenario, and 3.90 to 5.66/gal in the carinata oil scenario. With the addition of RINs and LCFS credits, the probability of loss was as low as 0.0%, 18.9%, and 74.6% in the brown grease, yellow grease, and carinata oil scenarios, respectively. However, without RIN or LCFS credits, the process was not found to be financially viable. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd